ANALISIS KESULITAN PEMAHAMAN KONSEP DAN PRINSIP MATERI POKOK DIMENSI TIGA SISWA KELAS XI SMK KEPERAWATAN YAHYA BIMA - Syahrir, Syahrir; Kusnadin, Kusnadin; Nurhayati, Nurhayati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2013)
The results of observations in class XI SMK Health Nursing Yahya Bima note that students still think that math is hard and scary that students often find it difficult when working on math problems. Student difficulties in learning mathematics are also characterized by low daily test results mathematics class XI student of SMK Nursing Yahya Bima. Therefore it is necessary to do an analysis of learning disability and the factors that influence the students’ learning difficulties in learning mathematics in particular three-dimensional. This research is a descriptive study conducted on 64 students of class XI SMK Yahya Nursing Bima. Data collected by the method of three-dimensional tests and questionnaires. Tests that have been declared valid and reliable research subjects used to determine which students who received grades of less than KKM defined as research subjects. Questionnaire is used to determine the internal factors and external factors that greatly affect the students’ learning difficulties in studying the three-dimensional. Data analysis techniques used in this research is descriptive qualitative and quantitative analysis. The results showed that as many as 33 students have difficulty in solving the three-dimensional, it is due to students ’difficulties in providing examples of specific concepts, students’ difficulty in giving up the name space, difficulties in classification, lessÂ skillsÂ students in basic skills, calculation errors, procedural errors , students are not mastering algorithms and do not understand the basic concepts. Factors - factors that cause learning difficulties students have great influence on quite a high level of learning difficulties experienced by students of class XI Vocational Nursing Yahya Way in three dimensions is the subject matter of interest, motivation, talent and intelligence of students who are on average relatively less and methods applied teachers including the use of visual aids in teaching the less even very low.